A three-dimensional finite element foot-ankle model and its personalisation methods analysis. (1st April 2022) - Mo, Fuhao; Li, Yuandong; Li, Junjie; Zhou, Shuangyuan; Yang, Zurong
Highlights: A three-dimensional finite element foot-ankle model with detailed anatomic structures was established and validated in dynamic gait loading by comparing a review of a series of gait experimental data. Two FE model personalization methods coupling MRI scan or optical scan with SWE measurements were comparatively analysed. A fast optical scan personalisation method of specific SWE measurement is a reasonable arrangement for subject-specific plantar deformation behaviour analysis. Abstract: Foot and ankle injuries are common as a result of overuse or trauma as well as various pathologies. This study aims to establish a three-dimensional foot-ankle model and investigate its suitability personalisation for the analysis of foot-ankle biomechanical responses during dynamic gait loading. The model was first established based on medical images and validated in both static standing posture and dynamic gait loading concerning regional plantar pressures and the centre of pressure curve (COP). Then, two model personalisation methods using magnetic resonance imaging (MRI) and fast optical scan data, respectively, were investigated and compared through analysing the dynamic gait responses of the scaled models. In both methods, material personalisation of plantar tissues was also combined through supersonic shear wave elastography (SWE) measurements. With regard to plantar pressure distribution and internal soft tissue strain, both personalisation methods correlated well with the subject-specific experimental results. Thus, we believe that the present model, with a fast optical scan personalisation method of specific SWE measurement, is a reasonable arrangement for subject-specific plantar deformation behaviour analysis during dynamic gait loading. Graphical Abstract: Image, graphical abstract